Luminescence and structural properties of defects in ion implanted ZnO - Monteiro, T.
ZnO substrates and films were intentionally implanted with rare earth and transition metal ions. The influence of the implantation and subsequent air thermal annealing treatments on the structural and optical properties of ZnO samples were studied by using Rutherford backscattering spectrometry and low temperature photoluminescence techniques. Intraionic Tm-related emission was observed for bulk and ZnO films. Similarly, Eu and Tb-doped ZnO films follow the same trend observed in bulk samples. No intraionic related emission was observed for Eu-doped samples even being the ion in Zn sites and for the Tb-doped samples ion segregation was observed for thermal annealing temperatures above 800°C. For the Mn-doped ZnO bulk samples the lattice recovery follows the same trend to that one observed for the Fe-doped samples, starting near 800°C being fully recovered at 1050°C. Although Fe3+ was observed no intraionic Mn-related emission was detected under the used conditions.